2016
DOI: 10.1038/ejhg.2016.157
|View full text |Cite
|
Sign up to set email alerts
|

The novel homozygous KCNJ10 c.986T>C (p.(Leu329Pro)) variant is pathogenic for the SeSAME/EAST homologue in Malinois dogs

Abstract: SeSAME/EAST syndrome is a multisystemic disorder in humans, characterised by seizures, sensorineural deafness, ataxia, developmental delay and electrolyte imbalance. It is exclusively caused by homozygous or compound heterozygous variations in the KCNJ10 gene. Here we describe a similar syndrome in two families belonging to the Malinois dog breed, based on clinical, neurological, electrodiagnostic and histopathological examination. Genetic analysis detected a novel pathogenic KCNJ10 c.986T4C (p.(Leu329Pro)) va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 46 publications
1
41
0
Order By: Relevance
“…Terriers with spinocerebellar ataxia, generalised myokymia and neuromyotonia have been identified to have a missense mutation in KCNJ10 (Gilliam and others 2014), a gene that encodes for an inwardly rectifying potassium channel resulting in spinocerebellar ataxia with myokymia, seizures or both (SAMS). The same mutation has been found in Belgian malinois shepherd dogs with myokymia and neuromyotonia (Van Poucke and others 2017). However, not all terriers with SAMS are homozygous for the KCNJ10 mutation, suggesting that other mutations are likely responsible for this presentation.…”
Section: Twitchessupporting
confidence: 70%
“…Terriers with spinocerebellar ataxia, generalised myokymia and neuromyotonia have been identified to have a missense mutation in KCNJ10 (Gilliam and others 2014), a gene that encodes for an inwardly rectifying potassium channel resulting in spinocerebellar ataxia with myokymia, seizures or both (SAMS). The same mutation has been found in Belgian malinois shepherd dogs with myokymia and neuromyotonia (Van Poucke and others 2017). However, not all terriers with SAMS are homozygous for the KCNJ10 mutation, suggesting that other mutations are likely responsible for this presentation.…”
Section: Twitchessupporting
confidence: 70%
“…This study revealed an unexpected genetic heterogeneity in clinically comparable cases, suggesting that more than one type of cerebellar ataxia is present in Belgian Shepherd dogs ( Kleiter et al 2011 ; Mauri et al 2017 ). The KCNJ10 variant was also identified in an independent study ( Stee et al 2016 ; Van Poucke et al 2017 ).…”
mentioning
confidence: 71%
“…In Belgian Shepherd dogs, a missense variant in KCNJ10 encoding a potassium channel causes spongy degeneration with cerebellar ataxia, subtype 1 (SDCA1, OMIA 002089–9615) [ 8 , 9 ]. The clinically similar SDCA2 in Belgian Shepherd dogs is due to a SINE insertion into ATP1B2 encoding the beta 2 subunit of the Na + /K + transporting ATPase (OMIA 002110–9615) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%